Formation of Game Competence of Preschool Children as a Component of Preparation for Learning Conditions in Nus - Saraieva, I.V. (Journal of Danubian Studies and Research, 2023)
The article highlights the theoretical and methodological foundations of the formation of preschool children’s play competence, which ensures the full readiness of the child to a new social status - the student. The game is characterized as a leading activity that involves the development of preschool children independence, individuality, organization, creativity, critical thinking, social unity, creativity, the formation of the ability to freedom of choice sustainable interest in the environment and self-realization in it. The game is an inexhaustible source of development of preschool children, contributing to the holistic development of the personality, since its components are motivational and intellectual urges and volitional efforts. The essence of the concepts of game, game activity, gaming competence is clarified. "Gaming competence" is presented as a dominant in the formation and flourishing of competencies that contribute to the knowledge of nature and the objective world and provide communication. Based on the analysis of research by scientists (L. Artemova, A. Bogush, L. Vygotsky, D. Elkonin, A. Korneeva, T. Pirozhenko, A. Usova, L. Franchuk, etc.), it was proved that the basis for the development of gaming competence is the general game of an adult with a child and the organization of a safe, interesting play environment aimed at stimulating and developing the child’s play desires. Characterized five characteristics of the game, presented in the study of foreign scientists (Jennifer M. Zosh, Emily J. Hopkins, Hanne Jensen, Claire Liu, Dave Neal, Cathy Hirsch-Pasek, S. Linnet Solis and David Whitebrade), which are an indicator of the interaction between an adult and child.